Evaluation of the Effectiveness of Emergency Management Training for Adult Nurses with a Prepost-Test Approach - Endang Soelistyowati; Woolnough Cale; Mahon Nitin; Meredith Tandon (Journal of World Future Medicine, Health and Nursing, 2024)
Emergency management is a key component in patient care that requires rapid and appropriate intervention. Effective training of nurses in this regard is essential to ensure competent and professional treatment. The proposed test approach is an evaluation method that can provide in-depth insight into the effectiveness of training in improving nurses' knowledge and skills in handling emergencies. This study aims to evaluate the effectiveness of emergency management training for adult nurses using a pre-post-test approach. The main focus of the research was to measure the increase in nurses' knowledge and skills after attending the training. This research method was carried out using a quantitative approach with a pre-post-test study design. Data was collected through knowledge tests before and after training, as well as direct observation of nurses' practical skills in handling emergencies. The results of this study indicate an increase in nurses' knowledge and skills after attending emergency management training. The average score on the knowledge test increased after training, indicating the effectiveness of training in increasing nurses' understanding of emergency management procedures. In addition, observations of nurses' practical skills also showed a significant improvement in their ability to handle emergencies. The conclusion of this study shows that emergency management training with a pre-post-test approach is effective in increasing the knowledge and skills of adult nurses. These results emphasize the importance of regular training and systematic evaluation of nurses' abilities in handling emergencies. Thus, recommendations are given to continue the development and implementation of similar training in an effort to improve the quality of emergency health services.